PENGARUH PELVIC ROCKING TERHADAP TINGKAT NYERI PUNGGUNG BAWAH PADA PEKERJA KONVEKSI DI DESA KAYEN PATI - Dina Novita Sari; Handayani, Prita Adisty; Rusmini, Sri (Jurnal Ilmu Keperawatan Komunitas, 2025)
Background: Low back pain is pain that often occurs in the back area of the lumbosacral area. Several factors, including age, gender, work duration, and education, can influence this back pain. Lower back pain also hurts the body because it can cause muscle tension, spasms, and obstructed blood flow. The causes of lower back pain that often occur are tissue damage, muscle injury, ligaments, sprains, and tiredness. Apart from that, poor posture can also cause lower back pain. This study aimed to determine the effect of pelvic rocking on lower back pain levels in convection workers in Kayen Village, Pati Regency. Method: The study took place between April 20 and May 13, 2024. This study used quantitative methods with a pre-experimental design, employing a pre- and post-test design strategy wherein the group received a pelvic rocking treatment. This study used 35 respondents as samples. This study used the Numeric Rating Scale (NRS) questionnaire instrument to measure the level of low back pain in respondents. Results: Based on the Wilcoxon statistical test, the results of this study showed that pelvic rocking has a significant influence on the level of lower back pain in convection workers in Kayen village, Pati Regency, with a p-value of 0.00 (<0.05). Conclusion: According to this study, pelvic rocking influences lower back pain. According to this study, convection workers should perform pelvic rocking exercises between breaks to prevent and reduce lower back pain.